Intelligent Computing and Information Science International Conference, ICICIS 2011, Chongqing, China, January 8-9, 2011. Proceedings, Part II - Chen, Ran.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This two-volume set (CCIS 134 and CCIS 135) constitutes the refereed proceedings of the International Conference on Intelligent Computing and Information Science, ICICIS2011, held in Chongqing, China, in January 2011. The 226 revised full papers presented in both volumes, CCIS 134 and CCIS 135, were carefully reviewed and selected from over 600 initial submissions. The papers provide the reader with a broad overview of the latest advances in the field of intelligent computing and information science.
Keywords: Computer science; Computer Communication Networks; Computer software; Database management; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Computer Communication Networks; Information Storage and Retrieval; Algorithm Analysis and Problem Complexity; Database Management